Straw return was more beneficial to improving saline soil quality and crop productivity than biochar in the short term - Ping Cong; Ping Cong; Jiashen Song; Jianxin Dong; Wenyan Su; Wenyan Su; Wenhao Feng; Hongyuan Zhang (Frontiers in Plant Science)
Salinized soil often exhibits high salt content and low nutrient availability, leading to the reduction of soil ecosystem function and crop productivity. Although straw return has profound effects on saline soil improvement, how soil quality index (SQI), soil ecosystem multifunctionality (EMF), and crop yield respond to different organic ameliorants remain unclear. Herein, a field experiment was established to explore the influence of various straw management strategies (no organic ameliorant, CK; corn straw return, CS; and corn straw biochar return; CB) on the saline soil functions and crop productivity. In relation to CK and CB, CS significantly improved SQI by 52% and 35%, respectively. This may be due to the decreased soil salt (especially soluble Na+) and increased available nutrients under corn straw return. Furthermore, CS increased soil EMF than CK by 71% and CB by 39%, which was caused by the increased activities of 1,4-β-glucosidase, β-1,4-N-acetyl-glucosaminidase, and leucine aminopeptidase. The linear model further supported that soil enzyme activities are positively related to available nutrient contents and negatively correlated with salt content. Moreover, the crop yield under CS significantly increased by 22% compared to CK. Also, soil quality positively influenced crop yield, with soil salt and available phosphorus being the primary influencing factors. However, crop yield was not sensitive to soil EMF. In summary, straw return was more beneficial to improving soil quality and crop productivity than biochar in the short term in saline soils.